Effect of Emotional Intelligence and Work Competence on Employee Performance - Vivy Limiyanty; Robin Robin (Institute of Computer Science (IOCS), 2022)
This study aims to determine whether there is an influence of emotional intelligence and competence on the performance of employees of PT. Universal Indofood Products Medan. The population in this study were all employees who worked at PT. Universal Indofood Product Medan as many as 214 employees. The sampling technique is to use the 5% significance Slovin technique where 139 employees will be used as samples. The results show that there is an effect partially or simultaneously where the emotional intelligence variable partially has a tcount value (5.827) greater than ttable (1.977) with a significant (0.00) less than 0.05, while the work competence variable has a tcount value. (6.142) is greater than ttable (1.977) with a significant (0.00) smaller than 0.05. Simultaneously, the variables of emotional intelligence and work competence have a value of Ftable (3.06) and a significance = 5% (0.05), namely Fcount (62.319) and sig.a (0.000a). This shows that the results of the study accept Ha and reject H0, while the coefficient of determination R Square is 0.746. This shows that the independent variables explain their influence on performance at PT. Universal Indofood Product Medan by 47.8%. While the remaining 52.2% is the influence of other independent variables.